Publication of Usage Rights Certificates on Ownership Land by the Regional Government for the Development of Public Facilities - Mustafa, Farid; Ilham Arisaputra, Muhammad (Fakultas Hukum Universitas Widya Mataram, 2022)
This study aims to determine the legal implications of the issuance of right of use certificates on land owned by individuals, as well as to determine the responsibility of the National Land Agency and the Gowa Regency Government for the issuance of certificates of use rights on land owned by individuals. This study uses an empirical legal research type, which examines and analyzes how the law works in the community. Research results (1) there are no rules governing the transfer of personal rights into state ownership, but in practice if such a thing happens, the legal basis used is Article 131 of the ART/BPN Ministerial Regulation Number 3 of 1997. Where the registration of the abolition of rights itself must accompanied by a statement of release of rights to the state which is signed before the Head of Regency/City BPN. (2) The BPN is also responsible for revoking/cancelling one of the certificates deemed invalid. Meanwhile, the local government of Gowa Regency is responsible for clearing the land without any burden on it. Keywords: Transfer of Land Rights, Use Rights, and Ownership Rights